Manajemen pemeliharaan mesin filler menggunakan metode Overall Equipment Effectiveness di production house area nursery PT. RAPP - Laila, Widya; Cahyani, Regita; Arsi, Fadli; Rahman, Arief Fazlul; Alfarisi, Salman (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Maintenance system is an activity conducted to ensure that machines or equipment are always ready to use. PT. RAPP uses a filler machine in the nursery area to fill cocopeat media into trays. The filler machine works optimally at a capacity of 600 kg (multiplied by two cycles) to fill 180 trays per day. When experiencing damage, this filler machine can only be used at a capacity of 300 kg (multiplied by four cycles) to fill 150-165 trays per day. To reduce machine downtime when there is damage, the implementation of machine maintenance management is needed. OEE is a method used to calculate machine effectiveness based on availability, performance, and quality. Using data from May 2022 to April 2023, the average OEE value obtained is 60.66%, indicating that the filler machine performance is below the standard of 85%. The calculation of the Six Big Losses shows that the values affecting machine performance are breakdown losses with a time loss of 22,825 minutes, rework losses with a time loss of 15.8 minutes, and setup and adjustment with a time loss of 41.8 minutes, indicating that the largest factor and the main cause affecting the OEE value of the filler machine is breakdown losses, which reduces the production rate.